A Simplified Thermal Model to Control the Energy Fluxes and to Improve the Performance of Buildings. (November 2016) - Danza, Ludovico; Belussi, Lorenzo; Meroni, Italo; Salamone, Francesco; Floreani, Fabio; Piccinini, Andrea; Dabusti, Alberto
Abstract: The article describes an accurate and suitable simplified tool aimed at evaluating, controlling and managing heat energy fluxes in buildings. The focus is the development of a Resistance-Capacitance (RC) thermal model able to represent the envelope thermal inertia on an hourly time basis. The single RC module simulates the thermal response of a single opaque or transparent element of the envelope. Each module consists of 3 Resistances and 2 Capacitances and is connected to the other modules by thermal nodes and coupled to an air internal temperature node in order to obtain a realistic exemplification of the specific boundary conditions and gains distribution in the conditioned space. The differential balance equations in each node have been solved with an explicit numerical method using Modelica simulation tool. A monitoring campaign was carried out on an outdoor test cell in order to observe the real thermal dynamic behaviour and the real hourly energy needs. The results of the model have been compared with the experimental collected data. The results are presented in terms of temperatures and heating power hourly profiles and cumulative daily energy needs. Finally the Bland-Altmann plot has been used to verify the accuracy and the shortcomings of the proposed thermal model.